Cigarette Smoking Is Associated with Prolongation of the QTc Interval Duration in Patients with Type 2 Diabetes Mellitus - Petros Thomakos; Stavros Liatis; Stavroula Kalopita; Ioannis Vlahodimitris; Chryssoula Stathi; Nicholas Katsilambros; Nicholas Tentolouris; Konstantinos Makrilakis (International Journal of Endocrinology)
Aims. Aim of the study was to evaluate the effect of smoking on autonomic nervous system (ANS) activity and QTc interval duration in patients with Type 2 diabetes mellitus (T2DM). Methods. A total of 70 patients with T2DM (35 chronic smokers, 35 nonsmokers) treated with oral antidiabetic medications underwent continuous ECG Holter monitoring for 24 hours and analysis of time- and frequency-domain measures of heart rate variability (HRV). HRV over short time was also assessed using the deep breathing test. In addition, baroreflex sensitivity (BRS) was evaluated using the spontaneous sequence method. The mean QTc interval was measured from the 24-hour ECG recordings. Results. Smokers had lower body mass index (BMI) and exhibited higher 24-hour mean heart rate. There was no difference regarding all measures of ANS activity between the two groups. Smokers showed increased mean QTc duration during the 24 hours (439.25±26.95 versus 425.05±23.03 ms, P=0.021) as well as in both day (439.14±24.31 ms, P=0.042) and night periods (440.91±32.30 versus 425.51±24.98 ms, P=0.033). The association between smoking status and mean QTc interval persisted after adjusting for BMI. Conclusions. Cigarette smoking is associated with prolongation of the QTc interval in patients with T2DM by a mechanism independent of ANS dysfunction.